DET ZOOFILE ÅRHUNDREDE - Knudsen, Anne (Tidsskriftet Antropologi, 1996)
Anne Knudsen: The Century of Zoophilia Taking as her point of departure the protests against a dying child having his last wish fulfilled because his wish was to kill a bear, the author argues that animals have achieved a higher moral status than that of humans during the 20th century. The status of animals (and of “nature”) is seen as a consequence of their muteness which on the one hånd makes it impossible for animals to lie, and which on the other hånd allows humans to imagine what animals would say, if they spoke. The development toward zoophilia is explained as a a logical consequence of the cultural naturalisation of humans, and the author draws the conclusion that we may end up entirely without animals as a category. This hypothetical situation will lead to juridical as well as philosophical complications.